Does psychological support, training and guidance for probation practitioners lead to improved outcomes for service users and staff? A systematic review of Offender Personality Disorder (OPD) Pathway community delivery - Aisling O’Meara; Carine Lewis; Jason Davies (PLoS ONE, 2025)
This review examines the evidence on outcomes for probation staff and the individuals under their supervision resulting from psychological training and support provided to staff. To be included, papers were required to evaluate impact on the outcomes of workforce development, wellbeing, risk and reconviction, or relationships. This review focussed on the frontline community delivery of a psychologically-informed programme designed for high risk of harm individuals presenting with complex needs; the Offender Personality Disorder (OPD) Pathway. Papers addressing impact of OPD interventions beyond core community delivery, or which addressed unrelated outcomes, were excluded from the review. The databases Scopus and EBSCO were searched on 19th October 2022 and titles were screened for inclusion by two reviewers. Quality of evidence was assessed by the Mixed Methods Appraisal Tool (MMAT). Due to the heterogenous nature of studies included, only narrative knowledge synthesis was possible and this was organised according to area of outcome explored and participant group. Twenty papers were included, comprising ten quantitative, two mixed, and eight qualitative methodologies (including three case studies). Workforce outcomes were the most frequently explored, with impacts noted in relation to self-reported confidence and competence. Impacts regarding risk and reconviction were limited both in relation to the number of studies addressing these outcomes and to the implications that could be drawn from these. Positive relational outcomes were reported as a result of OPD delivery, with consultation and formulation processes leading to better staff-offender relationships. The overall quality of evidence produced in the included studies was of a low to medium standard. Small sample sizes, high attrition rates, bespoke measures, and occasionally questionable analyses were some of the limitations noted. However, taking quality into account, findings were generally indicative of positive impacts of OPD community delivery, although regional differences in delivery model made generalisability of individual findings difficult.